Simplify this equation. (x) + (x+3) + (x-2) + 3(x+3) – 1 = 87

Question

Simplify this equation.

(x) + (x+3) + (x-2) + 3(x+3) – 1 = 87

0

Answers ( No )

  1. Charlotte
    0
    2021-09-10T20:41:51+00:00

    Expand it you get:
    x+x+3+x-2+3x+9-1-87=
    6x=78
    x=78/6 =13
    x=13

  2. Charlotte
    0
    2021-09-10T20:41:56+00:00

    x=13 simplify both sides of the equation, distribute,combine like terms, subtract 9 from both sides divide both sides by 6.

Leave an answer

Browse
Browse